Analisis Komparatif Aliran Khawarij, Mu’tazilah, dan Asy‘ariyah terhadap Pelaku Dosa Besar dalam Perspektif Pendidikan Akidah Islam - Yanto Maulana Restu; Muhammad Alfin Asy-Syakuuri; Nafilatul Mubarokah; Naswa Khairunisa; Tina Risdiyanti (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
In Islamic theology, the debate over the status of those who commit major sins (kabā'ir) is an important issue that greatly influences the formation of concepts of faith, deeds, and salvation.  Views on the status of those who commit major sins differ among the three main schools of thought: the Khawarij, the Mu'tazilah, and the Asy'ariyah.  While the Mu'tazilah consider them to be manzilah baina al-manzilatain—between believers and unbelievers—the Khawarij consider them to be unbelievers who have left Islam.  According to the Asy'ariyah, people who commit major sins remain believers, even though they are fāsiq, and their fate is ultimately decided by Allah. Using qualitative methodology and a literature review approach, this study analyzes the perspectives of these three schools of thought and their implications for Islamic creed education. The data collected came from primary and secondary literature discussing contemporary and classical Islamic theology. The analysis was conducted descriptively and comparatively to describe the conceptual differences between each school of thought and assess the pedagogical values that can be integrated into faith learning. The results of the study show that the differences in the views of the three schools of thought have theological and pedagogical consequences. Asy'ariyah offers space for spiritual rehabilitation and moderation, while Khawarij emphasizes moral firmness.  By teaching proportionally and comparatively, the three schools of thought can enrich faith education to shape students who are critical, moderate, and have good character.  This study confirms that a comparative theological approach in Islamic education is crucial to prevent extremism and create a balanced and contextual understanding of faith in today's world.   Keywords: Perpetrators of Major Sins, Islamic Theology, Khawarij, Mu'tazilah, and Asy'ariyah, Education in Faith, Religious Moderation